قاعدة ( المشقة تجلب التيسير ) - بودربالة فايزة; د/ مصطفى شريقن بن حبيب (جامعة عمار ثليجي الاغواط, 2016)
الملخص إفٌ قاعدة )ابؼشقة بذلب الهيستَ( من قواعد ابػمس الكليٌة ابؼهفق عليها ، كالتي يبتٌ عليها معظم مسائل ك أحكا ، ك فركع الشريعة الإسلامية،كبزهص بجميع الرخص الشرعية ، كإفٌ رفع ابغرج عن ابؼكلفتُ مقصد تشريعي،لأفٌ الأحكا معللة بجلب ابؼصالح كدرء ابؼفاسد ،كأفٌ القصد من الهكاليف الشرعية ىو حفظ مقاصدىا بُ ابػلق منها حفظ الضركريات ،كىي حفظ )الدين ،النفس،النسل،ابؼاؿ،كالعقل..( التي بنيت على عد ابغرج كالعنٌت. كمنها ابغاجيات التي تبتٌ على عدة قواعد أبنها )ابؼشقة بذلب الهيستَ( كىي أيضان تعمل على رفع ابغرج، كالهوسعة على ابؼكلفتُ .كمنها الهحسينيات التي أضفهها كبينت العلاقة التي بينها كبتُ القاعدة كأنّا مظهر من مظاىر الهخفيف كالهيستَ بابؼباحات.كأختَان بينت أثر تطبيق القواعد ابؼهفرعة عن القاعدة بُ فقو الأقليات ابؼسلمة بُ بلاد الغرب ،كالذم يعمل من خلالو ابؼفتي، كالمجههد، كالقاضي، من تغيتَ ابغكم الشرعي كفق تغتَ الزماف، كابؼكاف، كالأحواؿ، كالأعراؼ كابغاجات، كالضركرات، كابؼباحات. Abstract The rule of( hardship” almachaka” brings facilitating) ,is one of the five agreed total rules which most of the issues, provisions(ahkam) and the branches of the Islamic relegion are built upon it. t is specialized with ail the legal licenses of Al chariah, and taking the discomfiture(al haraj) away from “almokalafin is an intended legislative because the provisions are justified by bringing benefits and warding off evil The aim from the legal licenses is keeping its purposes in the creation .One among it, is keeping the necessaries the religion , the soul ,the progeny, the money, the brain....) which are bulit upon no discomfiture or harclship such as the needs (al hajiyat) which are built upon many rules, the most important rule is( the hardship brings facilitating )which works on taking the discomfiture away and expansion on “al mokalafin” like “altahsinat” which were added and showed its relationship between the rule, and it is a form from the forms of mitigation and facilitating with permitions, and finally it showed the effect of the rule application approaching from the rule of “fekeh al akaliyat almouslima’ in the western countries and which the moufti . al moujtahid and the judge work from in modifying the Islamic ruling “alhokem aichari” according to the changes of time, place ,situations ,customs, needs and permitions.
دراسة مقاصدية تطبيقية